2003
DOI: 10.1093/jn/133.6.1866
|View full text |Cite
|
Sign up to set email alerts
|

Weight Gain in Gonadectomized Normal and Lipoprotein Lipase–Deficient Male Domestic Cats Results from Increased Food Intake and Not Decreased Energy Expenditure

Abstract: Gonadectomy predisposes domestic cats to undesired body weight gain and obesity. The disturbance responsible for this disregulation of energy balance has not been clearly identified. Energy intake and expenditure, body composition and plasma concentrations of leptin, insulin, glucose and triacylglycerol were determined during a 36-wk period in adult male (2-5 y) gonadectomized (n = 8) and intact (n = 8) normal cats and gonadectomized (n = 8) and intact (n = 8) lipoprotein lipase (LPL)-deficient cats. Cats were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
88
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(106 citation statements)
references
References 42 publications
12
88
6
Order By: Relevance
“…Other researchers have noted that ovariohysterectomized or neutered cats have increased insulin and leptin concentrations, with no change in glucose or TG concentrations (compared to intact cats) (Fettman et al, 1997;Kanchuk et al, 2003). In the current study, food-restricted glucose concentrations increased from week 0 to 24, suggesting decreased insulin sensitivity with weight gain; however, food-restricted blood insulin concentrations did not change over time.…”
Section: High-protein Diet Following Ovariohysterectomycontrasting
confidence: 64%
See 3 more Smart Citations
“…Other researchers have noted that ovariohysterectomized or neutered cats have increased insulin and leptin concentrations, with no change in glucose or TG concentrations (compared to intact cats) (Fettman et al, 1997;Kanchuk et al, 2003). In the current study, food-restricted glucose concentrations increased from week 0 to 24, suggesting decreased insulin sensitivity with weight gain; however, food-restricted blood insulin concentrations did not change over time.…”
Section: High-protein Diet Following Ovariohysterectomycontrasting
confidence: 64%
“…Food intake and BW increased in all cats following ovariohysterectomy, as has been noted in other studies (Fettman et al, 1997;Harper et al, 2001;Kanchuk et al, 2003;Nguyen et al, 2004;Backus et al, 2007;Cave et al, 2007;Belsito et al, 2009). Earlier research has indicated that an estimated 20% to 30% reduction in food intake is needed to maintain BW of neutered cats (Flynn et al, 1996;Root et al, 1996;Belsito et al, 2009).…”
Section: High-protein Diet Following Ovariohysterectomysupporting
confidence: 63%
See 2 more Smart Citations
“…If pets weigh 20–30% more than their ideal body weight, they are classified as obese 1. Obesity in dog is associated with several health conditions including insulin resistance, pancreatitis, cruciate ligament rupture, and respiratory distress 2, 3. Bioactive peptides such as leptin, adiponectin, and pro‐inflammatory cytokines secreted from the adipose tissue are called adipokines 4.…”
mentioning
confidence: 99%